Tracking Fenestrae Dynamics in Live Murine Liver Sinusoidal Endothelial Cells - Zapotoczny, Bartlomiej; Szafranska, Karolina; Kus, Edyta; Braet, Filip; Wisse, Eddie; Chlopicki, Stefan; Szymonski, Marek (Hepatology (Baltimore, Md.), 2019)
The fenestrae of liver sinusoidal endothelial cells (LSECs) allow passive transport of solutes, macromolecules, and particulate material between the sinusoidal lumen and the liver parenchymal cells. Until recently, fenestrae and fenestrae‐associated structures were mainly investigated using electron microscopy on chemically fixed LSECs. Hence, the knowledge about their dynamic properties has remained to date largely elusive. Recent progress in atomic force microscopy (AFM) has allowed the study of live cells in three dimensions (X, Y, and Z) over a prolonged time (t) and this at unprecedented speeds and resolving power. Hence, we employed the latest advances in AFM imaging on living LSECs. As a result, we were able to monitor the position, size, and number of fenestrae and sieve plates using four‐dimensional AFM (X, Y, Z, and t) on intact LSECs in vitro. During these time‐lapse experiments, dynamic data were collected on the origin and morphofunctional properties of the filtration apparatus of LSECs. We present structural evidence on single laying and grouped fenestrae, thereby elucidating their dynamic nature from formation to disappearance. We also collected data on the life span of fenestrae. More especially, the formation and closing of entire sieve plates were observed, and how the continuous rearrangement of sieve plates affects the structure of fenestrae within them was recorded. We observed also the dawn and rise of fenestrae‐forming centers and defenestration centers in LSECs under different experimental conditions. Conclusion: Utilizing a multimodal biomedical high‐resolution imaging technique we collected fine structural information on the life span, formation, and disappearance of LSEC fenestrae; by doing so, we also gathered evidence on three different pathways implemented in the loss of fenestrae that result in defenestrated LSECs.